The antioxidant activity of Beta vulgaris leaf extract in improving scopolamine-induced spatial memory disorders in rats - Shadie Hajihosseini; Mahbubeh Setorki; Zahra Hooshmandi (Mashhad University of Medical Sciences, 2017)
Objective: Medicinal plants have attracted global attention due to their safety as well as their considerable antioxidant content that helps to prevent or ameliorate various disorders including memory impairments. This study was conducted to investigate the effect of beet root (Beta vulgaris) leaf extract on scopolamine-induced spatial memory impairments in male Wistar rats. Materials and Methods: Male Wistar rats were randomly divided into 5 groups (n=10): Control (C), scopolamine 1 mg/kg/day (S), scopolamine+50 mg/kg B. vulgaris leaf extract (S+B 50), scopolamine+100 mg/kg B. vulgaris leaf extract (S+B 100) and scopolamine+200 mg/kg B. vulgaris leaf extract (S+B 200). Morris water maze task was used to assess spatial memory. Serum antioxidant capacity and malondialdehyde (MDA) level were also measured. Results: Group S spent significantly less time in the target quadrant compared to the control group, and the administration of B. vulgaris leaf extract (100 and 200 mg/kg) significantly increased this time (p